The legends, the myths and the fables : Malay folklore in Singapore, 1965 - present - Ellysha Natasha Mahadi (Nanyang Technological University, 2021)
How has Malay folklore contributed to the national narrative about Singapore? To what extent did other agencies use Malay folklore and for what purpose? Growing up, most Singaporeans are probably familiar with tales about Sang Nila Utama, who has been credited for finding the land of Temasek and naming the island Singapura. However, other Malay folkloric figures who hold symbolic positions in the history of Singapore such as Badang, Radin Mas Ayu and Hang Nadim, are not discussed as often. Some of these tales had once been part of Malay court chronicles aimed to legitimise the rulers of the region from the fourteenth to sixteenth centuries, while some had been tragic stories that caught the attention of the Malay community. In recent years, non-Malay folks have been gaining awareness and knowledge about the aforementioned mythological figures because of the increasing usage of such tales in establishing Singapore’s past in the Malay World. This paper aims to uncover the different ways in which Malay folklore negotiates the spaces in Singapore and whether it fits within the idealised narrative about Singapore.